The efficiency of educational and healthcare public expenditures in Kosovo: A data envelopment analysis technique - Alban Elshani; Lekë Pula (Ekonomika, 2022)
This paper evaluates the performance and efficiency of the government public expenditure in the education and health sectors in the emerging economies context, specifically comparing Kosovo with the Western Balkan countries. The indicators of education and health sectors were used to assess a Public Sector Performance Index (PSP) and the Public Sector Efficiency Index (PSE). Also, this study uses the nonparametric method DEA (Data Envelopment Analysis) to evaluate the input-output oriented efficiency. This study finds that education score of performance ranges from 0.43 which is the minimum to 1.48 which is the maximum. And in the health sector, the PSP score ranges from 0.81 which is the minimum to 1.09 which is the maximum. Kosovo ranks 41st out of 42 countries in this sample, in terms of the education sector, with a performance index of 0.67, which is 37% below the average of 1.00, whilst in terms of the health sector it ranks 39th out of 42 countries in the sample. In the analysis of the input output efficiency model in the education sector, the results show that the countries included in the study achieve an efficiency of 76.69 and it means that countries can reduce relevant public expenditure by 23.3% and maintain the same level of PSP in the education sector. Kosovo is assessed in this analysis as an inefficient country. The value of the input-oriented index is 40.24, which means that Kosovo can achieve the same level of performance in the education sector by using 60% less relative public expenditure, whilst, on the other hand, the input-output efficiency results for the health sector show that the efficiency score for countries is 47.64, and denotes that the countries in the sample could reduce 53% in health expenditure to achieve the same performance in the health sector. Thus, Kosovo compared to other countries in the sample is within the limits of production opportunities and uses public expenditure on health and education inefficiently.
Keywords: 330; government public expenditure; health sector; education sector; Kosovo